(Self) tropicalism in Costa Rica: An analysis of the country-brand of the Costa Rican Tourism Institute within the geopolitics of tourism - Navarro Cerdas, Santiago (2020)
Currently, in the geopolitics of international tourism, the various regions of the planet prone to tourism are divided into specialized market clusters to attract the consumption of the experience, through "country brands". It is within this framework that the present discourse analysis of Corporate Social Responsibility, the Environmental Sustainability Certificates and the official propaganda of the Costa Rican Tourism Institute (ICT) in 2012, in which the stereotypes of the image of the tropic, nature tourism, sun and beach tourism are articulated with the rhetorical use of the image of the local population of Costa Rica as that of the "happiest country in the world", towards to makeup social, labor and cultural internal contradictions, following myths about Costa Rican exceptionalism. This reflects a clear global division, in which the world Centerst push the making of “peripheries of pleasure” (Ash and Turner, 1999) that are within the planet’s tropical geographic circuit, under specific imaginary exoticism (Beltrán, 2008), which we could name as “tropicalism”. Along with this, following the logic of “internal colonialism” (Amin, 2009), the political and economic elites of the Nation-State of these tropical regions develop what we could call "self-tropicalism", which is to build the image local similar to the desires of leisure and fantasy that global centers make up.